Science and Practice of Pediatric Critical Care Medicine - Wheeler, Derek S.; Wong, Hector R.; Shanley, Thomas P. (Springer London, 2009)
The field of critical care medicine is in the midst of a dramatic change. Technological and scientific advances during the last decade have resulted in a fundamental change in the way we view disease processes, such as sepsis, shock, acute lung injury, and traumatic brain injury. Pediatric intensivists have been both witness to and active participants in bringing about these changes and it is imperative that all physicians caring for critically ill children in this new era have a thorough understanding of the applicability of these modern developments to the care of patients at the bedside and to keep up with the rapidly evolving field of critical care medicine. The care of critically ill and injured children needs to be safe, evidence-based, equitable, efficient, timely, and family-centered. Science and Practice of Pediatric Critical Care Medicine discusses these changes in the specialty in greater scope and detail, offering the reader fresh insight into not only where we came from, but also where we are going as a specialty. Thus, this book is designed for all involved in the management of the pediatric critically ill patient, from physicians, residents and fellows in critical care, pulmonology, cardiology and pediatricians to specialist nurses and support personnel on the pediatric critical care unit and all medical professionals that are involved in the management of these patients.